Can contrast-enhanced ultrasound with second-generation contrast agents replace computed tomography angiography for distinguishing between occlusion and pseudo-occlusion of the internal carotid artery? (Clinics, 2015)
OBJECTIVE: The purpose of this study was to evaluate the effectiveness of contrast-enhanced ultrasound with a second-generation contrast agent in distinguishing between occlusion and pseudo-occlusion of the cervical internal carotid artery, comparing it with that of conventional Doppler ultrasound and the gold standard, computed tomography angiography. METHOD: Between June 2006 and June 2012, we screened 72 symptomatic vascular surgery outpatients at a public hospital. Among those patients, 78 cervical internal carotid arteries were previously classified as occluded by Doppler ultrasound (without contrast). The patients were examined again with Doppler ultrasound, as well as with contrast-enhanced ultrasound and computed tomography angiography. The diagnosis was based on the presence or absence of flow. RESULTS: Among the 78 cervical internal carotid arteries identified as occluded by Doppler ultrasound, occlusion was confirmed by computed tomography angiography in only 57 (73.1%), compared with 59 (77.5%) for which occlusion was confirmed by contrast-enhanced ultrasound (p>;0.5 vs. computed tomography angiography). Comparing contrast-enhanced ultrasound with Doppler ultrasound, we found that the proportion of cervical internal carotid arteries classified as occluded was 24.4% higher when the latter was used (p